2002
DOI: 10.1023/a:1016369114780
|View full text |Cite
|
Sign up to set email alerts
|

Do Internet‐Based Support Interventions Change Perceptions of Social Support?: An Experimental Trial of Approaches for Supporting Diabetes Self‐Management

Abstract: Internet-based support groups are a rapidly growing segment of mutual aid programs for individuals with chronic illnesses and other challenges. Previous studies have informed us about the content of online exchanges between support group members, but we know little about the ability of these interventions to change participants' perceptions of support. A randomized trial of 160 adult Type 2 diabetes patients provided novice Internet users with computers and Internet access to 1 of 4 conditions: (a) diabetes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
226
2
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(242 citation statements)
references
References 22 publications
5
226
2
6
Order By: Relevance
“…The information they provide about themselves reduces anonymity, but participants seldom meet, even vicariously through one-to-one e-mail interactions. Despite the absence of face-to-face interaction, as rich as it is with nonverbal cues of emotion, involvement, and personal-even visceral-identification, anonymous supportive interaction online is linked to perceptions of social support and reports of social support received for health and other concerns (50)(51)(52). Online interaction is still interaction, even when it is delayed for minutes, hours, or days.…”
Section: Provide Social Connections Relevant To Cancer Prevention Andmentioning
confidence: 99%
“…The information they provide about themselves reduces anonymity, but participants seldom meet, even vicariously through one-to-one e-mail interactions. Despite the absence of face-to-face interaction, as rich as it is with nonverbal cues of emotion, involvement, and personal-even visceral-identification, anonymous supportive interaction online is linked to perceptions of social support and reports of social support received for health and other concerns (50)(51)(52). Online interaction is still interaction, even when it is delayed for minutes, hours, or days.…”
Section: Provide Social Connections Relevant To Cancer Prevention Andmentioning
confidence: 99%
“…They are mostly neutral, positive, or supportive. Patients obviously try to be helpful in the encounter with others, and this even more so in the TF (Barrera et al 2002). But, there are also negative or even detrimental comments, like 'this group is good for nothing' or 'I am better than the rest of you'.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Barrera et al 56 showed that the Internet is actually perceived by its users as an effective source of support. In a randomized trial, 160 novice Internet users with type 2 diabetes (53% female; mean age 59.3 ± 9.4 years) were assigned to four Webbased conditions: diabetes information only, a personal self-management coach, or one of two interventions combining coaching and support.…”
Section: Using New Technologies For Groupsmentioning
confidence: 99%